Cardiometabolic Protection Mediated by Phyllostachys nigra Polysaccharides via Gut Microbiota–Inflammation Axis - Antonio R. Bergman; Haitong Shao; Aentonio E. Greene; Jeal Perry (International Journal of Clinical and Translational Medicine, 2026)
The escalating global burden of cardiometabolic disease demands a reexamination of intervention strategies through the lens of complex systems theory. This paper reframes the mechanism of Phyllostachys nigra polysaccharides not as a linear biochemical pathway, but as a distributed modulation of the gut microbiota–inflammation axis, a large-scale biological infrastructure with profound implications for host metabolic governance. By treating the intestinal microbiome as a decentralized, self-regulating network with emergent properties, we analyze how polysaccharide-derived molecular signals reconfigure microbial community architecture, reduce systemic inflammation, and enhance cardiometabolic resilience. Drawing on principles of infrastructure robustness, fault tolerance, and adaptive governance, we dissect the structural trade-offs between short-chain fatty acid production, gut barrier integrity, and immune effector calibration. We further evaluate the deployment readiness of such polysaccharide interventions through the lens of population-level health systems, addressing scalability, equitable access, and regulatory policy frameworks. The analysis reveals that the intervention’s efficacy depends on context-sensitive modular integration with existing dietary and pharmacological infrastructures, and that its sustainability hinges on maintaining microbial diversity and functional redundancy. Through this synthesis, we demonstrate that systems-level thinking offers a powerful vocabulary for understanding and optimizing host-microbe interactions, positioning polysaccharide-based strategies as a flexible, modulatory component within the broader architecture of precision public health. The paper concludes by outlining a research agenda that aligns molecular mechanism elucidation with infrastructure-aware deployment, bridging the gap between laboratory discovery and societal implementation.